Follow up through Endoscopical – Histological Studies and Helicobacter Pylori Infections in Patients Suffering from Gastric Ulcers - Marcos Félix Osorio Pagola; Antonio Moré Pérez; Libán Álvarez Cáceres; Juan Luis de Pasos Carrazana; Anagalys Ortega Alvelay (Medisur)
Background: Endoscopic follow up of gastric ulcers until healing has a great important due to the possibility of a new proliferation. The commonest chronic infection worldwide is caused by Helicobacter pylori and it is associated to gastro duodenal diseases. Objective: To determine the endoscopic-biopsic follow up and to set the frequency of infection due to Helicobacter pylori in those patients who suffer from gastric ulcers. Methods: observational, descriptive and prospective study carried out at the University Hospital “Arnaldo Milián Castro”. It included 96 gastric ulcer sufferers diagnosed endoscopically and who fulfilled with the selection criteria. Endoscopy and biopsy of the gastric mucosa was done for the histological study of the gastric ulcers and for the diagnosis of infection due to Helicobacter pylori through hematoxiline-eosine and giemsa stains respectively. Results: 89 patients (92,7 %) healed their ulcers in the first three months of follow up and 5 patients underwent a histological diagnosis of malignant ulcers (5,2 %). Surgery was done on the two patients whose ulcers did not heal. (2,1 %). 67,7 % had been infected with the bacteria. There was a greater frequency of patients infected with Helicobacter pylori, either with benign or malignant ulcus (93,8 % y 6,2 %) respectively. Conclusions: the follow up of benign ulcers was good , almost all of them healed in a three-month follow up. 5 patients suffered from malignant ulcers, being 2 of them diagnosed in their second endoscopy. More than half of the patients were infected with Helicobacter pylori.